An ozone catalytic oxidation system for the degradation of organic compounds in secondary wastewater from refining and chemical processes - Ma, Jun (Environmental technology, 2023)
To overcome the low catalytic efficiency, insufficient catalyst strength, and poor ozone circulation in the advanced treatment of secondary wastewater, a hollow cylindrical Fe-Cu-Ce-Mn/Al2O3 catalyst was prepared by the step impregnation method. Compared with the common impregnation method, the step impregnation method produced a more uniform and compact distribution of each metal element, which was more conducive to generating the synergistic effect of various metals; thus, increasing the mineralization rate of organic matter. The hollow cylindrical design ensured the strength of the catalyst and the circulation of ozone. The reduction of the chemical oxygen demand (COD) was compared under different experimental conditions, with the optimal conditions found to be an ozone contact time of 40 min and ozone dosage of 40 mg/L. The average COD, ammonia nitrogen, and ultraviolet absorbance at 254 nm (UV254) removal rates were 36%, 19%, and 20%, respectively. After 3 weeks of continuous experiment, the removal rate was still high. Following analysis by three dimensional fluorescence, GC-MS, and the molecular weight detection of water samples before and after treatment, it was found that the catalyst enhanced the effect of ozone on wastewater treatment, with a significant removal of tryptophan-like aromatic proteins and soluble microbial metabolites, and the removal of most of the small molecular organic matter. In addition, part of the refractory organic matter could be converted into easily degradable organic matter, which greatly improved the biodegradability and mineralization rate of wastewater, and provided good conditions for subsequent treatment